Is the New Injury Severity Score (NISS) a better outcome predictor than the Injury Severity Score (ISS) in patients with musculoskeletal injuries: A retrospective analysis? - Osita Ede; Chisom O. Uzuegbunam; Oke R. Obadaseraye; Kenechi A. Madu; Cajetan U. Nwadinigwe; Chijioke C. Agu; Udo E. Anyaehie; Emmanuel C. Iyidobi (Journal of Orthopaedics, Trauma and Rehabilitation, 2023)
Purpose: The Injury Severity Score (ISS) is used to predict outcome after trauma. However, it is criticised because of flaws in its calculation of injury severity. The New Injury Severity Score (NISS) was proposed as an alternative. However, studies are conflicted on which is better. We compared both scales in predicting surgery, multiple surgeries, preoperative blood transfusion, hospital stay length and mortality in patients with orthopaedic injuries. Method: A retrospective cohort study that used the hospital's trauma database. Patients’ data were extracted, and the outcome parameters noted. The ISS and NISS were calculated for each patient. The patients were dichotomised into discrepant and non-discrepant if both scores are different or the same, respectively. A receiver operator characteristic (ROC) curve was generated for each outcome parameter, and the area under the curve (AUC) compared between the two scoring systems. Results: Four hundred and forty-seven (447) patients participated in this study. The participants’ average age was 34.78 years (SD = 18.67), mean ISS score was 8.5 (SD = 5.9), while the average NISS was 9.4 (SD = 6.6). The NISS exceeded the ISS (discrepant) in 82 subjects (18.3%), while both scores are the same (non-discrepant) in 365 subjects (81.7%). The NISS outperformed the ISS in predicting multiple surgeries and hospital stay length, while the ISS better predicts mortality rate. Both performed similarly for predicting surgical intervention and blood transfusion. Conclusion: Both scores performed similarly and there is insufficient evidence to replace ISS with NISS.